2021
DOI: 10.1186/s13000-021-01091-6
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated colonic neoplasm with SMARCA4 germline gene mutation and loss of SMARCA4 protein expression: a case report and literature review

Abstract: Background Nonsense mutation or inactivation of SMARCA4 (BRG1) is associated with a monomorphic undifferentiated histological appearance in tumors at different sites. The association between SMARCA4 alteration and undifferentiated colonic carcinoma needs to be further elucidated. Methods A 61-year-old male patient presented to the hospital with intermittent epigastric pain in the right upper abdomen and abdominal distension. The enhanced computed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The second patient had risk factors for esophageal carcinoma while the first patient had a positive family history, which highlights the possibility of a germline mutation. Duan et al reported a patient with SMARCA4-deficient undifferentiated colonic carcinoma due to a germline SMARCA4 gene mutation, who had a second-degree relative with colon cancer at age 50 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second patient had risk factors for esophageal carcinoma while the first patient had a positive family history, which highlights the possibility of a germline mutation. Duan et al reported a patient with SMARCA4-deficient undifferentiated colonic carcinoma due to a germline SMARCA4 gene mutation, who had a second-degree relative with colon cancer at age 50 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, germline pathogenic variants in SMARCA4 have been reported to be related to the predisposition of several types of cancers, namely Small Cell Carcinoma of the Ovary, Hypercalcemic Type (SCCOHT), early onset Ovarian Cancer (OC), neuroblastoma, and rhabdoid tumor predisposition syndrome [ 34 , 35 , 36 ]. Germline mutations at SMARCA4 that cause a truncated protein are reported to be the key genetic event because a decrease in functional BRG1 protein is expected and has often been related to such cancer pathologies as SMARCA4-deficient Non-Small-Cell-Lung Cancer (NSCLC) and rhabdoid tumor predisposition syndrome [ 35 , 37 , 38 , 39 ]. Indeed, pathogenic variants in the SMARCA4 gene are mainly associated with early onset (≤40 years) OC [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to what has been examined so far in the association between pathogenic mutations in SMARCA4 and early onset in SCCOHT and NSCLC, there are currently no close correlations in the literature with this gene and CRC, particularly in young people (EOCRC), therefore necessitating further investigation to find potential linkages [ 37 ]. However, variants in genes not closely related to colon cancer are instead to be considered with more interest in patients with early onset, as different studies are being conducted to better understand the molecular basis of juvenile forms of CRC [ 5 ], which is important knowledge for therapeutic assets.…”
Section: Resultsmentioning
confidence: 99%
“…Our patient on the most recent clinical follow-up is 1) is extremely broad and includes NUT carcinoma, melanoma, neuroendocrine neoplasm, myoepithelial carcinoma, SMARCA4-deficient neoplasms, synovial sarcoma, and plasma cell neoplasm. [19][20][21][22][23][24][25][26][27][28][29][30] Immunohistochemical stains and/or molecular testing will be essential. That said, the tumor immunoreactivity with NUT comes with a caveat.…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis based on the epithelioid and rhabdoid/plasmacytoid morphology (Table 1) is extremely broad and includes NUT carcinoma, melanoma, neuroendocrine neoplasm, myoepithelial carcinoma, SMARCA4‐deficient neoplasms, synovial sarcoma, and plasma cell neoplasm 19–30 . Immunohistochemical stains and/or molecular testing will be essential.…”
Section: Discussionmentioning
confidence: 99%